Bacterial terpene biosynthesis: challenges and opportunities for pathway engineering - Helfrich, Eric J. N.; Lin, Geng-Min; Voigt, Christopher A.; Clardy, Jon (Beilstein Journal of Organic Chemistry, 2019)
Terpenoids are the largest and structurally most diverse class of natural products. They possess potent and specific biological activity in multiple assays and against diseases, including cancer and malaria as notable examples. Although the number of characterized terpenoid molecules is huge, our knowledge of how they are biosynthesized is limited, particularly when compared to the well-studied thiotemplate assembly lines. Bacteria have only recently been recognized as having the genetic potential to biosynthesize a large number of complex terpenoids, but our current ability to associate genetic potential with molecular structure is severely restricted. The canonical terpene biosynthetic pathway uses a single enzyme to form a cyclized hydrocarbon backbone followed by modifications with a suite of tailoring enzymes that can generate dozens of different products from a single backbone. This functional promiscuity of terpene biosynthetic pathways renders terpene biosynthesis susceptible to rational pathway engineering using the latest developments in the field of synthetic biology. These engineered pathways will not only facilitate the rational creation of both known and novel terpenoids, their development will deepen our understanding of a significant branch of biosynthesis. The biosynthetic insights gained will likely empower a greater degree of engineering proficiency for non-natural terpene biosynthetic pathways and pave the way towards the biotechnological production of high value terpenoids.
Keywords: bacterial sesquiterpenes and diterpenes; cytochrome P450; pathway engineering; synthetic biology; terpene biosynthesis; terpene cyclase

(untitled) - Yamada, Y.; Kuzuyama, T.; Komatsu, M.; Shin-ya, K.; Omura, S.; Cane, D. E.; Ikeda, H. (Proc. Natl. Acad. Sci. U. S. A., 2015)

(untitled) - Chappell, J. (Annu. Rev. Plant Physiol. Plant Mol. Biol., 1995)

(untitled) - Gershenzon, J.; Dudareva, N. (Nat. Chem. Biol., 2007)

(untitled) - Wani, M. C.; Taylor, H. L.; Wall, M. E.; Coggon, P.; McPhail, A. T. (J. Am. Chem. Soc., 1971)

(untitled) - Tu, Y. (Angew. Chem., Int. Ed., 2016)

Natural Products - Drug Discovery and Therapeutic Medicine - Wang, G. T. W.; Bidigare, R. R. (Terpenoids As Therapeutic Drugs and Pharmaceutical Agents, 2005)

(untitled) - Fischbach, M. A.; Walsh, C. T. (Chem. Rev., 2006)

(untitled) - Hertweck, C. (Angew. Chem., Int. Ed., 2009)

(untitled) - Austin, M. B.; O'Maille, P. E.; Noel, J. P. (Nat. Chem. Biol., 2008)

(untitled) - Driller, R.; Janke, S.; Fuchs, M.; Warner, E.; Mhashal, A. R.; Major, D. T.; Christmann, M.; Bruck, T.; Loll, B. (Nat. Commun., 2018)

(untitled) - Dickschat, J. S. (Nat. Prod. Rep., 2016)

Biotechnology of Isoprenoids - Janocha, S.; Schmitz, D.; Bernhardt, R. (Terpene Hydroxylation with Microbial Cytochrome P450 Monooxygenases, 2015)

(untitled) - Donehower, R. C. (Oncologist, 1996)

(untitled) - Kingston, D. G. I. (Chem. Commun., 2001)

(untitled) - Wender, P. A.; Badham, N. F.; Conway, S. P.; Floreancig, P. E.; Glass, T. E.; Houze, J. B.; Krauss, N. E.; Lee, D.; Marquess, D. G.; McGrane, P. L.; Meng, W.; Natchus, M. G.; et al. (J. Am. Chem. Soc., 1997)

(untitled) - Wender, P. A.; Badham, N. F.; Conway, S. P.; Floreancig, P. E.; Glass, T. E.; Gränicher, C.; Houze, J. B.; Jänichen, J.; Lee, D.; Marquess, D. G.; McGrane, P. L.; Meng, W.; et al. (J. Am. Chem. Soc., 1997)

(untitled) - Mendoza, A.; Ishihara, Y.; Baran, P. S. (Nat. Chem., 2012)

(untitled) - Lin, X.; Hezari, M.; Koepp, A. E.; Floss, H. G.; Croteau, R. (Biochemistry, 1996)

(untitled) - Wildung, M. R.; Croteau, R. (J. Biol. Chem., 1996)

(untitled) - Jennewein, S.; Croteau, R. (Appl. Microbiol. Biotechnol., 2001)

(untitled) - Wuts, P. G. (Curr. Opin. Drug Discovery Dev., 1998)

(untitled) - Lodzki, M.; Godin, B.; Rakou, L.; Mechoulam, R.; Gallily, R.; Touitou, E. (J. Controlled Release, 2003)

(untitled) - Leweke, F. M.; Piomelli, D.; Pahlisch, F.; Muhl, D.; Gerth, C. W.; Hoyer, C.; Klosterkötter, J.; Hellmich, M.; Koethe, D. (Transl. Psychiatry, 2012)

(untitled) - Devinsky, O.; Cilio, M. R.; Cross, H.; Fernandez-Ruiz, J.; French, J.; Hill, C.; Katz, R.; Di Marzo, V.; Jutras-Aswad, D.; Notcutt, W. G.; Martinez-Orgado, J.; Robson, P. J.; et al. (Epilepsia, 2014)

(untitled) - Mechoulam, R.; Peters, M.; Murillo-Rodriguez, E.; Hanuš, L. O. (Chem. Biodiversity, 2007)

(untitled) - Challis, G. L.; Ravel, J.; Townsend, C. A. (Chem. Biol., 2000)

(untitled) - Stachelhaus, T.; Mootz, H. D.; Marahiel, M. A. (Chem. Biol., 1999)

(untitled) - Phelan, V. V.; Du, Y.; McLean, J. A.; Bachmann, B. O. (Chem. Biol., 2009)

(untitled) - Reeves, C. D.; Murli, S.; Ashley, G. W.; Piagentini, M.; Hutchinson, C. R.; McDaniel, R. (Biochemistry, 2001)

(untitled) - Jenner, M.; Afonso, J. P.; Bailey, H. R.; Frank, S.; Kampa, A.; Piel, J.; Oldham, N. J. (Angew. Chem., Int. Ed., 2015)

(untitled) - Helfrich, E. J. N.; Ueoka, R.; Dolev, A.; Rust, M.; Meoded, R. A.; Bhushan, A.; Califano, G.; Costa, R.; Gugger, M.; Steinbeck, C.; Moreno, P.; Piel, J. (Nat. Chem. Biol., 2019)

(untitled) - Jensen, K.; Niederkrüger, H.; Zimmermann, K.; Vagstad, A. L.; Moldenhauer, J.; Brendel, N.; Frank, S.; Pöplau, P.; Kohlhaas, C.; Townsend, C. A.; Oldiges, M.; Hertweck, C.; et al. (Chem. Biol., 2012)

(untitled) - Yeh, E.; Kohli, R. M.; Bruner, S. D.; Walsh, C. T. (ChemBioChem, 2004)

(untitled) - Ueoka, R.; Uria, A. R.; Reiter, S.; Mori, T.; Karbaum, P.; Peters, E. E.; Helfrich, E. J. N.; Morinaka, B. I.; Gugger, M.; Takeyama, H.; Matsunaga, S.; Piel, J. (Nat. Chem. Biol., 2015)

(untitled) - Crüsemann, M.; Kohlhaas, C.; Piel, J. (Chem. Sci., 2013)

(untitled) - Jenke-Kodama, H.; Dittmann, E. (Phytochemistry, 2009)

(untitled) - Gao, Y.; Honzatko, R. B.; Peters, R. J. (Nat. Prod. Rep., 2012)

(untitled) - Firn, R. D.; Jones, C. G. (Nat. Prod. Rep., 2003)

(untitled) - Jones, C. G.; Firn, R. D. (Philos. Trans. R. Soc., B, 1991)

(untitled) - Fischbach, M. A.; Clardy, J. (Nat. Chem. Biol., 2007)

(untitled) - Nett, R. S.; Montanares, M.; Marcassa, A.; Lu, X.; Nagel, R.; Charles, T. C.; Hedden, P.; Rojas, M. C.; Peters, R. J. (Nat. Chem. Biol., 2017)

(untitled) - Hedden, P.; Phillips, A. L.; Rojas, M. C.; Carrera, E.; Tudzynski, B. (J. Plant Growth Regul., 2001)

(untitled) - Blin, K.; Pascal Andreu, V.; de los Santos, E. L. C.; Del Carratore, F.; Lee, S. Y.; Medema, M. H.; Weber, T. (Nucleic Acids Res., 2019)

(untitled) - Medema, M. H.; Kottmann, R.; Yilmaz, P.; Cummings, M.; Biggins, J. B.; Blin, K.; de Bruijn, I.; Chooi, Y. H.; Claesen, J.; Coates, R. C.; Cruz-Morales, P.; Duddela, S.; et al. (Nat. Chem. Biol., 2015)

Biosynthesis - Aromatic Polyketides, Isoprenoids, Alkaloids - Davis, E. M.; Croteau, R. (Cyclization Enzymes in the Biosynthesis of Monoterpenes, Sesquiterpenes, and Diterpenes, 2000)

(untitled) - Chen, K.; Baran, P. S. (Nature, 2009)

(untitled) - Maimone, T. J.; Baran, P. S. (Nat. Chem. Biol., 2007)

(untitled) - Blin, K.; Shaw, S.; Steinke, K.; Villebro, R.; Ziemert, N.; Lee, S. Y.; Medema, M. H.; Weber, T. (Nucleic Acids Res., 2019)

(untitled) - Medema, M. H.; Blin, K.; Cimermancic, P.; de Jager, V.; Zakrzewski, P.; Fischbach, M. A.; Weber, T.; Takano, E.; Breitling, R. (Nucleic Acids Res., 2011)

(untitled) - Christianson, D. W. (Chem. Rev., 2006)

(untitled) - Christianson, D. W. (Curr. Opin. Chem. Biol., 2008)

(untitled) - Wendt, K. U.; Schulz, G. E. (Structure, 1998)

(untitled) - Baunach, M.; Franke, J.; Hertweck, C. (Angew. Chem., Int. Ed., 2015)

(untitled) - Baer, P.; Rabe, P.; Fischer, K.; Citron, C. A.; Klapschinski, T. A.; Groll, M.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2014)

(untitled) - Dickschat, J. S. (Angew. Chem., Int. Ed., 2019)

(untitled) - Smanski, M. J.; Peterson, R. M.; Huang, S.-X.; Shen, B. (Curr. Opin. Chem. Biol., 2012)

(untitled) - Wang, C.-M.; Cane, D. E. (J. Am. Chem. Soc., 2008)

(untitled) - von Reuss, S.; Domik, D.; Lemfack, M. C.; Magnus, N.; Kai, M.; Weise, T.; Piechulla, B. (J. Am. Chem. Soc., 2018)

(untitled) - Hillwig, M. L.; Zhu, Q.; Liu, X. (ACS Chem. Biol., 2014)

(untitled) - Erickson, H. K.; Poulter, C. D. (J. Am. Chem. Soc., 2003)

(untitled) - Carter-Franklin, J. N.; Parrish, J. D.; Tschirret-Guth, R. A.; Little, R. D.; Butler, A. (J. Am. Chem. Soc., 2003)

(untitled) - Carter-Franklin, J. N.; Butler, A. (J. Am. Chem. Soc., 2004)

(untitled) - Awakawa, T.; Zhang, L.; Wakimoto, T.; Hoshino, S.; Mori, T.; Ito, T.; Ishikawa, J.; Tanner, M. E.; Abe, I. (J. Am. Chem. Soc., 2014)

(untitled) - Xu, Z.; Baunach, M.; Ding, L.; Hertweck, C. (Angew. Chem., Int. Ed., 2012)

(untitled) - Chooi, Y.-H.; Hong, Y. J.; Cacho, R. A.; Tantillo, D. J.; Tang, Y. (J. Am. Chem. Soc., 2013)

(untitled) - Taura, F.; Morimoto, S.; Shoyama, Y.; Mechoulam, R. (J. Am. Chem. Soc., 1995)

(untitled) - Lichman, B. R.; Kamileen, M. O.; Titchiner, G. R.; Saalbach, G.; Stevenson, C. E. M.; Lawson, D. M.; O’Connor, S. E. (Nat. Chem. Biol., 2019)

(untitled) - Cane, D. E.; Weiner, S. W. (Can. J. Chem., 1994)

(untitled) - He, X.; Cane, D. E. (J. Am. Chem. Soc., 2004)

(untitled) - Jiang, J.; He, X.; Cane, D. E. (J. Am. Chem. Soc., 2006)

(untitled) - Jiang, J.; Cane, D. E. (J. Am. Chem. Soc., 2008)

(untitled) - Lin, X.; Cane, D. E. (J. Am. Chem. Soc., 2009)

(untitled) - Rabe, P.; Barra, L.; Rinkel, J.; Riclea, R.; Citron, C. A.; Klapschinski, T. A.; Janusko, A.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2015)

(untitled) - Rinkel, J.; Lauterbach, L.; Rabe, P.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2018)

(untitled) - Rabe, P.; Rinkel, J.; Dolja, E.; Schmitz, T.; Nubbemeyer, B.; Luu, T. H.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2017)

(untitled) - Dickschat, J. S.; Pahirulzaman, K. A. K.; Rabe, P.; Klapschinski, T. A. (ChemBioChem, 2014)

Consequences of Microbial Interactions with Hydrocarbons, Oils, and Lipids: Production of Fuels and Chemicals - Wong, J.; Rios-Solis, L.; Keasling, J. D. (Microbial Production of Isoprenoids, 2017)

(untitled) - Martin, V. J. J.; Pitera, D. J.; Withers, S. T.; Newman, J. D.; Keasling, J. D. (Nat. Biotechnol., 2003)

(untitled) - Anthony, J. R.; Anthony, L. C.; Nowroozi, F.; Kwon, G.; Newman, J. D.; Keasling, J. D. (Metab. Eng., 2009)

(untitled) - Ajikumar, P. K.; Xiao, W.-H.; Tyo, K. E. J.; Wang, Y.; Simeon, F.; Leonard, E.; Mucha, O.; Phon, T. H.; Pfeifer, B.; Stephanopoulos, G. (Science, 2010)

(untitled) - Dürr, C.; Schnell, H.-J.; Luzhetskyy, A.; Murillo, R.; Weber, M.; Welzel, K.; Vente, A.; Bechthold, A. (Chem. Biol., 2006)

(untitled) - Smanski, M. J.; Peterson, R. M.; Rajski, S. R.; Shen, B. (Antimicrob. Agents Chemother., 2009)

Cytochrome P450 - Structure, Mechanism, and Biochemistry - Ortiz de Montellano, P. R. (Substrate Oxidation by Cytochrome P450 Enzymes, 2015)

(untitled) - Denisov, I. G.; Makris, T. M.; Sligar, S. G.; Schlichting, I. (Chem. Rev., 2005)

(untitled) - Hannemann, F.; Bichet, A.; Ewen, K. M.; Bernhardt, R. (Biochim. Biophys. Acta, Gen. Subj., 2007)

(untitled) - Atkinson, J. T.; Campbell, I.; Bennett, G. N.; Silberg, J. J. (Biochemistry, 2016)

(untitled) - Ortega Ugalde, S.; de Koning, C. P.; Wallraven, K.; Bruyneel, B.; Vermeulen, N. P. E.; Grossmann, T. N.; Bitter, W.; Commandeur, J. N. M.; Vos, J. C. (Appl. Microbiol. Biotechnol., 2018)

(untitled) - Rudolf, J. D.; Chang, C.-Y.; Ma, M.; Shen, B. (Nat. Prod. Rep., 2017)

(untitled) - Kim, S.-Y.; Zhao, P.; Igarashi, M.; Sawa, R.; Tomita, T.; Nishiyama, M.; Kuzuyama, T. (Chem. Biol., 2009)

(untitled) - Rudolf, J. D.; Dong, L.-B.; Manoogian, K.; Shen, B. (J. Am. Chem. Soc., 2016)

(untitled) - Duan, L.; Jogl, G.; Cane, D. E. (J. Am. Chem. Soc., 2016)

(untitled) - Huo, L.; Hug, J. J.; Fu, C.; Bian, X.; Zhang, Y.; Müller, R. (Nat. Prod. Rep., 2019)

(untitled) - Rutledge, P. J.; Challis, G. L. (Nat. Rev. Microbiol., 2015)

(untitled) - Baltz, R. H. (J. Ind. Microbiol. Biotechnol., 2010)

(untitled) - Gomez-Escribano, J. P.; Bibb, M. J. (Microb. Biotechnol., 2011)

(untitled) - Khalid, A.; Takagi, H.; Panthee, S.; Muroi, M.; Chappell, J.; Osada, H.; Takahashi, S. (ACS Synth. Biol., 2017)

(untitled) - Myronovskyi, M.; Rosenkränzer, B.; Nadmid, S.; Pujic, P.; Normand, P.; Luzhetskyy, A. (Metab. Eng., 2018)

(untitled) - Takamatsu, S.; Lin, X.; Nara, A.; Komatsu, M.; Cane, D. E.; Ikeda, H. (Microb. Biotechnol., 2011)

(untitled) - Brill, Z. G.; Condakes, M. L.; Ting, C. P.; Maimone, T. J. (Chem. Rev., 2017)

(untitled) - Razzak, M.; De Brabander, J. K. (Nat. Chem. Biol., 2011)

(untitled) - Davies, H. M. L. (Nature, 2009)

(untitled) - Zhou, Q.; Chen, X.; Ma, D. (Angew. Chem., Int. Ed., 2010)

(untitled) - Molawi, K.; Delpont, N.; Echavarren, A. M. (Angew. Chem., Int. Ed., 2010)

(untitled) - Major, D. T. (Nat. Catal., 2018)

(untitled) - Davies, H. M. L.; Manning, J. R. (Nature, 2008)

(untitled) - Mello, R.; Fiorentino, M.; Fusco, C.; Curci, R. (J. Am. Chem. Soc., 1989)

(untitled) - Costas, M.; Mehn, M. P.; Jensen, M. P.; Que, L. (Chem. Rev., 2004)

(untitled) - Groves, J. T.; Bonchio, M.; Carofiglio, T.; Shalyaev, K. (J. Am. Chem. Soc., 1996)

(untitled) - Brodsky, B. H.; Du Bois, J. (J. Am. Chem. Soc., 2005)

(untitled) - Yang, J.; Gabriele, B.; Belvedere, S.; Huang, Y.; Breslow, R. (J. Org. Chem., 2002)

(untitled) - Chen, M. S.; White, M. C. (Science, 2007)

(untitled) - Ishihara, Y.; Baran, P. S. (Synlett, 2010)

(untitled) - Willot, M.; Christmann, M. (Nat. Chem., 2010)

(untitled) - Meguro, A.; Tomita, T.; Nishiyama, M.; Kuzuyama, T. (ChemBioChem, 2013)

(untitled) - Rabe, P.; Pahirulzaman, K. A. K.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2015)

(untitled) - Schifrin, A.; Khatri, Y.; Kirsch, P.; Thiel, V.; Schulz, S.; Bernhardt, R. (Org. Biomol. Chem., 2016)

(untitled) - Lauterbach, L.; Rinkel, J.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2018)

(untitled) - Rinkel, J.; Lauterbach, L.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2017)

(untitled) - Aaron, J. A.; Lin, X.; Cane, D. E.; Christianson, D. W. (Biochemistry, 2010)

(untitled) - Li, R.; Chou, W. K. W.; Himmelberger, J. A.; Litwin, K. M.; Harris, G. G.; Cane, D. E.; Christianson, D. W. (Biochemistry, 2014)

(untitled) - Blank, P. N.; Barrow, G. H.; Chou, W. K. W.; Duan, L.; Cane, D. E.; Christianson, D. W. (Biochemistry, 2017)

(untitled) - Tomita, T.; Kim, S.-Y.; Teramoto, K.; Meguro, A.; Ozaki, T.; Yoshida, A.; Motoyoshi, Y.; Mori, N.; Ishigami, K.; Watanabe, H.; Nishiyama, M.; Kuzuyama, T. (ACS Chem. Biol., 2017)

(untitled) - Görner, C.; Häuslein, I.; Schrepfer, P.; Eisenreich, W.; Brück, T. (ChemCatChem, 2013)

(untitled) - Peters, R. J. (Nat. Prod. Rep., 2010)

(untitled) - Jia, M.; Potter, K. C.; Peters, R. J. (Metab. Eng., 2016)

(untitled) - Andersen-Ranberg, J.; Kongstad, K. T.; Nielsen, M. T.; Jensen, N. B.; Pateraki, I.; Bach, S. S.; Hamberger, B.; Zerbe, P.; Staerk, D.; Bohlmann, J.; Møller, B. L.; Hamberger, B. (Angew. Chem., Int. Ed., 2016)

(untitled) - Jia, M.; Mishra, S. K.; Tufts, S.; Jernigan, R. L.; Peters, R. J. (Metab. Eng., 2019)

(untitled) - Mafu, S.; Jia, M.; Zi, J.; Morrone, D.; Wu, Y.; Xu, M.; Hillwig, M. L.; Peters, R. J. (Proc. Natl. Acad. Sci. U. S. A., 2016)

(untitled) - Hernandez-Ortega, A.; Vinaixa, M.; Zebec, Z.; Takano, E.; Scrutton, N. S. (Sci. Rep., 2018)

(untitled) - Jung, S. T.; Lauchli, R.; Arnold, F. H. (Curr. Opin. Biotechnol., 2011)

(untitled) - Dietrich, J. A.; Yoshikuni, Y.; Fisher, K. J.; Woolard, F. X.; Ockey, D.; McPhee, D. J.; Renninger, N. S.; Chang, M. C. Y.; Baker, D.; Keasling, J. D. (ACS Chem. Biol., 2009)

(untitled) - Seifert, A.; Vomund, S.; Grohmann, K.; Kriening, S.; Urlacher, V. B.; Laschat, S.; Pleiss, J. (ChemBioChem, 2009)

(untitled) - Paramasivan, K.; Mutturi, S. (Crit. Rev. Biotechnol., 2017)

(untitled) - Harada, H.; Yu, F.; Okamoto, S.; Kuzuyama, T.; Utsumi, R.; Misawa, N. (Appl. Microbiol. Biotechnol., 2009)

(untitled) - Westfall, P. J.; Pitera, D. J.; Lenihan, J. R.; Eng, D.; Woolard, F. X.; Regentin, R.; Horning, T.; Tsuruta, H.; Melis, D. J.; Owens, A.; Fickes, S.; Diola, D.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2012)

(untitled) - Alonso-Gutierrez, J.; Chan, R.; Batth, T. S.; Adams, P. D.; Keasling, J. D.; Petzold, C. J.; Lee, T. S. (Metab. Eng., 2013)

(untitled) - Leonard, E.; Ajikumar, P. K.; Thayer, K.; Xiao, W.-H.; Mo, J. D.; Tidor, B.; Stephanopoulos, G.; Prather, K. L. J. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Tashiro, M.; Kiyota, H.; Kawai-Noma, S.; Saito, K.; Ikeuchi, M.; Iijima, Y.; Umeno, D. (ACS Synth. Biol., 2016)

(untitled) - Zhu, F.; Zhong, X.; Hu, M.; Lu, L.; Deng, Z.; Liu, T. (Biotechnol. Bioeng., 2014)

(untitled) - Alonso-Gutierrez, J.; Kim, E.-M.; Batth, T. S.; Cho, N.; Hu, Q.; Chan, L. J. G.; Petzold, C. J.; Hillson, N. J.; Adams, P. D.; Keasling, J. D.; Garcia Martin, H.; Lee, T. S. (Metab. Eng., 2015)

(untitled) - Biggs, B. W.; Lim, C. G.; Sagliani, K.; Shankar, S.; Stephanopoulos, G.; De Mey, M.; Ajikumar, P. K. (Proc. Natl. Acad. Sci. U. S. A., 2016)

(untitled) - Meyer, A. J.; Segall-Shapiro, T. H.; Glassey, E.; Zhang, J.; Voigt, C. A. (Nat. Chem. Biol., 2019)

(untitled) - Dahl, R. H.; Zhang, F.; Alonso-Gutierrez, J.; Baidoo, E.; Batth, T. S.; Redding-Johanson, A. M.; Petzold, C. J.; Mukhopadhyay, A.; Lee, T. S.; Adams, P. D.; Keasling, J. D. (Nat. Biotechnol., 2013)

(untitled) - Korman, T. P.; Opgenorth, P. H.; Bowie, J. U. (Nat. Commun., 2017)

(untitled) - Kirby, J.; Nishimoto, M.; Chow, R. W. N.; Baidoo, E. E. K.; Wang, G.; Martin, J.; Schackwitz, W.; Chan, R.; Fortman, J. L.; Keasling, J. D. (Appl. Environ. Microbiol., 2015)

(untitled) - Chatzivasileiou, A. O.; Ward, V.; Edgar, S. M.; Stephanopoulos, G. (Proc. Natl. Acad. Sci. U. S. A., 2019)

(untitled) - Ye, L.; Zhang, C.; Bi, C.; Li, Q.; Zhang, X. (Microb. Cell Fact., 2016)

(untitled) - Alonso‐Gutierrez, J.; Koma, D.; Hu, Q.; Yang, Y.; Chan, L. J. G.; Petzold, C. J.; Adams, P. D.; Vickers, C. E.; Nielsen, L. K.; Keasling, J. D.; Lee, T. S. (Biotechnol. Bioeng., 2018)

(untitled) - Lin, G.-M.; Warden-Rothman, R.; Voigt, C. A. (Curr. Opin. Syst. Biol., 2019)

Biotechnology of Isoprenoids - Pateraki, I.; Heskes, A. M.; Hamberger, B. (Cytochromes P450 for Terpene Functionalisation and Metabolic Engineering, 2015)

(untitled) - Chang, M. C. Y.; Eachus, R. A.; Trieu, W.; Ro, D.-K.; Keasling, J. D. (Nat. Chem. Biol., 2007)

(untitled) - Gricman, Ł.; Weissenborn, M. J.; Hoffmann, S. M.; Borlinghaus, N.; Hauer, B.; Pleiss, J. (ChemistrySelect, 2016)

(untitled) - Kosuri, S.; Church, G. M. (Nat. Methods, 2014)

(untitled) - Casini, A.; Storch, M.; Baldwin, G. S.; Ellis, T. (Nat. Rev. Mol. Cell Biol., 2015)

(untitled) - Gibson, D. G.; Young, L.; Chuang, R.-Y.; Venter, J. C.; Hutchison, C. A., III; Smith, H. O. (Nat. Methods, 2009)

(untitled) - Engler, C.; Gruetzner, R.; Kandzia, R.; Marillonnet, S. (PLoS One, 2009)

(untitled) - Luo, X.; Reiter, M. A.; d’Espaux, L.; Wong, J.; Denby, C. M.; Lechner, A.; Zhang, Y.; Grzybowski, A. T.; Harth, S.; Lin, W.; Lee, H.; Yu, C.; et al. (Nature, 2019)